From Sugar to Revolution: Women's Visions of Haiti, Cuba, and the Dominican Republic - Harms, Patricia (Labour / Le Travail, 2014)
This article reviews the book, "From Sugar to Revolution: Women's Visions of Haiti, Cuba, and the Dominican Republic," by Myriam J.A. Chancy.